Measuring the Satisfaction Index of Bumi Rasa Program Using Survey Method: A Case Study Damar Village, East Belitung Regency - Retno Suryani; Nugroho Budi Susilo; Mohamad Ridhwan; Firna Nabila; Nadya Suci Fauzul Azhima; Annisa Sila Puspita (Universitas Diponegoro, 2023)
Bumi Rasa is a community empowerment program conducted by PT. Timah Tbk Primary Tin Production Unit. This community empowerment is undertaken in the Damar village, East Belitung Regency. The program consists of several programs, namely catering, stationery, traditional cakes, cleaning services, and laundry. The Bumi Rasa program has a significant impact on the economic and environmental development of the village. Therefore, this study analyzes the satisfaction level of the program using the satisfaction index survey method. This study aims to measure the satisfaction level of the recipients of the community development program. The Bumi Rasa program received a satisfaction index of 3.06 from the community, which converted to a satisfaction index of 76.67, indicating that the community is very satisfied with the program